Urbanism, urbanisation, health and human biology: an introduction - Schell, L; Ulijaszek, S (Cambridge University Press, 1999)
The world is becoming an increasingly urban place. Current estimates indicate that one half of the world's population will be living in urban centers by the year 2005, largely the result of two centuries of rapid urbanisation, and there are no apparent social forces that strongly oppose it...